Manajemen Kompetensi Kepribadian Guru al-Quran Hadits di MAN 1 Banyumas - Nurfuadi Nurfuadi (Journal on Education, 2023)
Competence is an ability to carry out a job that is based on skills and knowledge and is supported by the work attitude required by the job. The purpose of this paper is to analyze the personality competency management of Al-Quran Hadith teachers at MAN 1 Banyumas. This research is qualitative with research results namely the development of the quality of learning at Madrasah Aliyah Negeri 1 Banyumas including after the material is discussed per sub-chapter once chapter I is finished discussing until the UTS or PTS activities are completed then they are billed for memorizing Hadith and Surahs in Juz Ama adjusted with chapters discussed in thematic models, for example in grade 10 on the last theme, namely: Humans as caliphs fil ard and grade 11 with the theme: Life is blessed by respecting parents and teachers and in grade 12 with the theme: Love to support the poor. After the two chapters have been studied, an assessment is carried out through repetition activities with a total of 10 questions taken from the LKS, then followed by a final semester exam / PAS (End of Semester Assessment) in odd semesters and then a final exam for even semester or with a new term is called with PAT (Year End Assessment). While the evaluation is carried out by the head of the madrasa to teachers through scheduled supervision activities for each teacher. In each new academic year, at least twice the principal supervises the teacher, namely in the middle of the odd semester and the middle of the even semester.